WOMEN’S AUTONOMY AND UNINTENDED PREGNANCY: AN IDHS 2017 DATA ANALYSIS - Margareth Maya Parulianta Naibaho; Desy Nuri Fajarningtiyas; Riza Fatma Arifa; Andi Pancanugraha (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
Unintended pregnancy impacts hugely on maternal and child health. This study aimed to examine the influence of women’s autonomy on unintended pregnancies including unwanted and mistimed pregnancies. Using the Indonesia Demographic and Health Survey (IDHS) 2017, this study analyzed 12,624 currently married women who had birth within five years preceding the survey. Women’s autonomy was constructed from several variables related to women’s decision on obtaining health care, visiting family, and spending large household purchase. The result of logistic regression analysis showed that women’s autonomy affected significantly on unintended pregnancy after controlling other variables. However, it implied a negative correlation in which autonomous women were 1.3 more likely to experience unintended pregnancy than their counterparts. Both parity and birth interval showed the biggest influences on unintended pregnancy; the odds ratios were 2.7 and 3.1 respectively. Women who married at age 21 years and above, lived in rural areas and decided the number of children to have with husbands tended to have a lower risk facing an unintended pregnancy. Improving IEC and counseling about family planning and reproductive health is expected to increase couples’ knowledge. Therefore, the decisions on the number of children and contraceptive use can be made jointly and unintended pregnancy will be prevented.